A Polymorphism in the FGFR4 Gene Is Associated With Risk of Neuroblastoma and Altered Receptor Degradation. Issue 2 (March 2016) - Whittle, Sarah B.; Reyes, Sahily; Du, Melissa; Gireud, Monica; Zhang, Linna; Woodfield, Sarah E.; Ittmann, Michael; Scheurer, Michael E.; Bean, Andrew J.; Zage, Peter E.
Abstract : Background: Outcomes for children with high-risk neuroblastoma are poor, and improved understanding of the mechanisms underlying neuroblastoma pathogenesis, recurrence, and treatment resistance will lead to improved outcomes. Aberrant growth factor receptor expression and receptor tyrosine kinase signaling are associated with the pathogenesis of many malignancies. A germline polymorphism in the FGFR4 gene is associated with increased receptor expression and activity and with decreased survival, treatment resistance, and aggressive disease for many malignancies. We therefore investigated the role of this FGFR4 polymorphism in neuroblastoma pathogenesis. Materials and Methods: Germline DNA from neuroblastoma patients and matched controls was assessed for the FGFR4 Gly/Arg388 polymorphism by RT-PCR. Allele frequencies were assessed for association with neuroblastoma patient outcomes and prognostic features. Degradation rates of the FGFR4 Arg388 and Gly388 receptors and rates of receptor internalization into the late endosomal compartment were measured. Results: Frequency of the FGFR4 AA genotype and the prevalence of the A allele were significantly higher in patients with neuroblastoma than in matched controls. The Arg388 receptor demonstrated slower degradation than the Gly388 receptor in neuroblastoma cells and reduced internalization into multivesicular bodies. Conclusions: The FGFR4 Arg388 polymorphism is associated with an increased prevalence of neuroblastoma in children, and this association may be linked to differences in FGFR4 degradation rates. Our study provides the first evidence of a role for FGFR4 in neuroblastoma, suggesting that FGFR4 genotype and the pathways regulating FGFR4 trafficking and degradation may be relevant for neuroblastoma pathogenesis. Abstract : Supplemental Digital Content is available in the text.